Analisis Bibliometrik: Peranan Akuntansi Lingkungan Terhadap Kinerja Keuangan Dan Kinerja Lingkungan Perusahaan - Mirna Distiyah; Ivan Gunadi; Manda Dewi Sautri; Cherlin Khalidanallah; Nashikatulhiroti; Nabil FR (Journal of Literature Review, 2026)
This study aims to analyze the development of research on the role of environmental accounting in financial performance and corporate environmental performance using a bibliometric approach based on Scopus data from 2020–2026. A total of 517 articles were analyzed using VOSviewer software to identify publication trends, research themes, and keyword relationships. The results show that environmental accounting publications have continued to increase, with Environmental, Social, and Governance (ESG) and environmental performance emerging as the dominant themes. In addition, new topics such as digital innovation, sustainable finance, and ESG impact prediction have emerged as future research directions. These findings indicate that environmental accounting plays an important role in supporting corporate sustainability as well as improving financial and environmental performance.